Giant placental chorioangioma presenting as severe polyhydramnios: a case report - Agrawal, Prabha; Agrawal, Rahul; S. Fareed, Shabnam; R. Ancha, Kinnera (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Chorioangiomas are the most common non-trophoblastic, benign, vascular tumour of the hemochorial placenta. Small chorioangiomas are usually symptomless, and of no clinical significance while giant ones more than 4 cm in diameter may be complicated by polyhydramnios, foetal cardiomegaly, hydrops fetalis, and foetal growth restriction. We present a case of a 32-year-old primigravida referred to us at 30 weeks of gestation with large placental chorioangioma causing polyhydramnios which was treated by amnioreduction twice over 1 month. On referral the tumour size was about 56 mm size with severe polyhydramnios with amniotic fluid index of 57 cm, with breathlessness and pain abdomen. After relevant investigations and informed consent, she was taken up for caesarean section. 2 litres of clear liquor drained. She delivered a live female baby weighing 1.2 kg with Apgar score of 7 and 8. Patient stood the operation well. Gross and microscopic examination of the placenta confirmed the diagnosis of chorioangioma. Chorioangioma should be considered as differential diagnosis in cases of hydrops fetalis or polyhydramnios. Doppler ultrasound is the method of choice to detect chorioangioma and its vascularity. Giant chorioangiomas complicating pregnancy can be managed conservatively with close surveillance, foetal monitoring and timely intervention to prevent maternal and foetal morbidity and mortality.